Kampung Pangan Berseri Program as an Effort to Overcome Malnourished Children in Balikpapan City - Abdul Gassing; Catur Yogi Prasetyo; Nico Ferianzo; Fitri Ulul Azizah; Anisa Nur Jannah (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The Berseri Food Village Program (PKPB) is a program initiated by PT Pertamina Patra Niaga Integrated Terminal (IT) Balikpapan through the Corporate Social Responsibility (CSR) scheme which aims to address the problem of malnutrition in Balikpapan City. The Berseri Food Village program has important components in this program including basic nutrition education, and management of PMT Mandiri to fulfill basic nutrition, ecoschool camps, and food self-sufficiency through urban farming. The method used in this research is descriptive with a qualitative approach. Data obtained from various sources were analyzed in depth to be able to describe the overall implementation, benefits and impacts, as well as evaluation of the PKPM program. The results of the study show that PKPB has succeeded in increasing the availability of food and nutrition in the people of Balikpapan City. This program has also succeeded in increasing public awareness about improving the nutritional quality of children in Balikpapan City and increasing public awareness in an effort to protect the environment by increasing urban food self-sufficiency.